2022
DOI: 10.3847/1538-4357/ac923b
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Compact 15–33 GHz Radio Continuum Sources in Local U/LIRGs

Abstract: We present the analysis of ∼100 pc scale compact radio continuum sources detected in 63 local (ultra)luminous infrared galaxies (U/LIRGs; L IR ≥ 1011 L ⊙), using FWHM ≲ 0.″1–0.″2 resolution 15 and 33 GHz observations with the Karl G. Jansky Very Large Array. We identify a total of 133 compact radio sources with effective radii of 8–170 pc, which are classified into four main categories—“AGN” (active galactic nuclei), “AGN/SBnuc” (AGN-starburst composite nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 177 publications
0
9
0
Order By: Relevance
“…We extract spectra from 10 regions of interest within the channel 1 FOV to investigate IR-bright sources resolved in the MIRI imaging as well as diffuse emission surrounding those sources and in the eastern nucleus (Figure 1). We chose five locations coincident with the two brightest IR sources, the NE and SW cores ((a), (c)), and several bright clumps identified in the MIRI imaging data and in both the submillimeter and radio ((d), (e), and (f)) (Saito et al 2018;Evans et al 2022;Song et al 2022). We also chose five regions intended to capture diffuse emission between (b) and around ((g), (h), (i), and (j)) the bright clumps coincident with some tidal and shock features previously identified using ALMA (Saito et al 2017(Saito et al , 2018.…”
Section: Miri Mrs Datamentioning
confidence: 99%
“…We extract spectra from 10 regions of interest within the channel 1 FOV to investigate IR-bright sources resolved in the MIRI imaging as well as diffuse emission surrounding those sources and in the eastern nucleus (Figure 1). We chose five locations coincident with the two brightest IR sources, the NE and SW cores ((a), (c)), and several bright clumps identified in the MIRI imaging data and in both the submillimeter and radio ((d), (e), and (f)) (Saito et al 2018;Evans et al 2022;Song et al 2022). We also chose five regions intended to capture diffuse emission between (b) and around ((g), (h), (i), and (j)) the bright clumps coincident with some tidal and shock features previously identified using ALMA (Saito et al 2017(Saito et al , 2018.…”
Section: Miri Mrs Datamentioning
confidence: 99%
“…The canonical and well-studied ULIRG Arp 220, for example, has regions forming stars at surface densities of Σ SFR ∼ 10 4.1±0.1 M yr −1 kpc −2 (Barcos- Muñoz et al 2015). On the other hand, Song et al (2022) found predominantly sub-Eddington star formation in a broader sample of local luminous infrared galaxies (LIRGs; L IR = 10 11−12 L ) and ULIRGs. If the extreme hyper-luminous IR galaxies (HyLIRGs; L IR > 10 13 L ) seen at high-z like the PASSAGES objects are in fact sub-Eddington, it might suggest simply that their orderof-magnitude increase in IR luminosity over ULIRGs is accompanied by a comparable ∼ 0.5 dex increase in radius.…”
Section: Resultsmentioning
confidence: 99%
“…However, angular resolution plays a critical role in this measurement, as it may be possible for objects to be sub-Eddington on global, galaxy-integrated scales but super-Eddington in local regions of dense star formation, as suggested by Simpson et al (2015a) and Barcos-Muñoz et al (2017). For example, for local ULIRGs, Song et al (2022) found radio continuum clumps smaller than 100 pc with large surface densities up to Σ SFR ≈ 1600 M e yr −1 kpc −2 .…”
Section: Eddington-limited Star Formation Surface Densities?mentioning
confidence: 99%